Strategi Personal Branding Konten Kreator Melalui Media Sosial Tikok - Erika Yosita Putri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
In this digital era, social media, especially TikTok, has become a favored medium among the Indonesian public. TikTok has emerged as one of the social media platforms with a broad reach for sharing various types of information. Many TikTok users have become content creators, utilizing TikTok to disseminate their content. This study aims to determine the communication strategies of film review content creators to build personal branding and secure collaborations with production houses. This research employs qualitative methods and a case study approach. The case study approach is used to provide an in-depth description of how the creator @adhehdyt manages and develops strategies related to personal branding through data collected via interviews, social media content analysis, and the collection of the creator’s documentation.. Keywords: Personal Branding, Tiktok, @adhehdyt, Social Media,Communication